Encapsulation of Diclofenac Molecules into Poly(ε-Caprolactone) Electrospun Fibers for Delivery Protection. (12th November 2009) - Tammaro, Loredana; Russo, Giuseppina; Vittoria, Vittoria
Abstract : Mg-Al Hydrotalcite-like clay (LDH) intercalated with diclofenac anions (HTlc-DIC) was introduced into poly(ε -caprolactone) (PCL) in different concentrations by the electrospinning technique, and mats of nonwoven fibers were obtained and compared to the pristine pure electrospun PCL. The fibers, characterized by X-ray diffraction, thermogravimetric analysis, and differential scanning calorimetry, show an exfoliated clay structure up to 3 wt%, a good thermal stability of the diclofenac molecules and a crystallinity of PCL comparable to the pure polymer. The scanning electron microscopy revealed electrospun PCL and PCL composite fibers diameters ranging between 500 nm to 3.0 μ m and a generally uniform thickness along the fibers. As the results suggested the in vitro drug release from the composite fibers is remarkably slower than the release from the corresponding control spun solutions of PCL and diclofenac sodium salt. Thus, HTlc-DIC/PCL fibrous membranes can be used as an antinflammatory scaffold for tissue engineering.